EFFECT OF STORAGE TEMPERATURE ON THE ASCORBIC ACID CONTENT, TOTAL PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY IN LETTUCE (LACTUCA SATIVA L.) - C. Serea; O. Barna; M. Manley; M. Kidd (Journal of Animal and Plant Sciences, 2014)
The effect of storage temperature (0, 2, 4 and 6 °C) and time (0, 3, 6, 9, 12 and 15 days) on ascorbic acid content, total phenolic content and antioxidant activity of three lettuce cultivars (Roderick, Markies and Locarno) was studied to determine optimal storage conditions. All parameters present in this study – ascorbic acid content, total phenolic content and antioxidant activity – were studied by spectrophotometric assays. The Folin-Ciocalteu assay was used to determine total phenolic content, while antioxidant activity was tested using ABTS assay. After 15 days of storage ascorbic acid content ranged from 6.47 to 2.93 mg / 100 g fresh weight (fw) total phenolic content ranged from 3.83 to 2.27 mg (GAE)/g fw and antioxidant activity ranged from 432.03 to 158.53 µM TEAC/g fw. The optimal storage conditions were between 0 °C and 2 °C up to 6 days. A correlation between temperature and duration of storage was found among cultivars. Statistical analyses showed specific variations for each cultivar analysed.
Keywords: Lactuca sativa L.; ascorbic acid content; total phenolic content; antioxidant activity; storage; temperature